2009
DOI: 10.1093/cvr/cvp217
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cardiac proteasome subtypes differ in their susceptibility to proteasome inhibitors

Abstract: These data show that different inhibitors have differential inhibitory effects on the various cardiac proteasome subtypes. Different cardiac subtypes are inhibited by the same dose of proteasome inhibitor to a different extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 53 publications
3
43
0
Order By: Relevance
“…The abundance of intermediate proteasomes β5i in human liver and colon is in line with the previous detection of high amounts of subunit β5i with low amounts of β1i and β2i in these tissues (25). Human heart mostly contained standard proteasomes, in line with a recent study performed in rat heart (24).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The abundance of intermediate proteasomes β5i in human liver and colon is in line with the previous detection of high amounts of subunit β5i with low amounts of β1i and β2i in these tissues (25). Human heart mostly contained standard proteasomes, in line with a recent study performed in rat heart (24).…”
Section: Discussionsupporting
confidence: 90%
“…Intermediate proteasomes were observed in transfected cells and were suggested to partly account for the heterogeneity of proteasome preparations isolated from rat muscle, which displayed varying physicochemical and functional properties and contained varying compositions in catalytic β subunits (18)(19)(20)(21)(22)(23). Such heterogeneity was also observed in rodent heart (20,24) and in human colon and liver (25). Posttranslational modifications, such as phopshorylation, acetylation, or methylation, were suggested to also contribute to this heterogeneity (20,22,26,27).…”
mentioning
confidence: 99%
“…Briefly, this consists of the following steps: a fractionated protein precipitation with ammonium sulphate, chromatography on DEAE-Sephacel, gel filtration on Superose 6 and anion exchange chromatography on Mono Q. In the last purification step, a hydrophobic interaction chromatography was performed on a Resource-Phe column for separation of proteasome subpopulations (Kloss et al 2009). …”
Section: Purification Of 20s Proteasomes and Separation Of Proteasomementioning
confidence: 99%
“…We have shown previously that proteasomes of rat liver all comprised intermediate-type subunit compositions (Dahlmann et al 2000;Schmidt et al 2006). Taking advantage of their different surface hydrophobicity, we separated 20S proteasomes from rat heart into three subpopulations two of them comprising intermediate-type and one containing standard proteasomes (Kloss et al 2009). In the present investigation, we found that 20S proteasomes from liver of young and aged rats could also be separated into three subpopulations.…”
Section: Introductionmentioning
confidence: 99%
“…The latter protect 3'UTRs of RNA from endonucleolytic degradation. 56 To avoid this complication, the protease activity of proteasomes was inactivated by either incubation with MG132 inhibitor 57 or with ethanol wash prior to their addition to A431 cells. The completeness of proteasomal inactivation by MG132 or signals have been shown to change the phosphorylation state of proteasomes.…”
Section: S Proteasome Exhibits Endoribonuclease Activity Controlledmentioning
confidence: 99%